BODIPY‐Labeled Cyclobutanes by Secondary C(sp3)−H Arylations for Live‐Cell Imaging. Issue 55 (13th September 2019) - Virelli, Matteo; Wang, Wei; Kuniyil, Rositha; Wu, Jun; Zanoni, Giuseppe; Fernandez, Antonio; Scott, Jamie; Vendrell, Marc; Ackermann, Lutz
Abstract: Arylated cyclobutanes were accessed by a versatile palladium‐catalyzed secondary C(sp 3 )−H activation, exploiting chelation assistance by modular triazoles. The C−H arylation led to cyclobutane natural product derivatives in a highly regioselective fashion, setting the stage for the easy access to novel fluorogenic boron‐dipyrrin (BODIPY)‐labeled probes for live‐cell imaging. Abstract : Suitable for live‐cell imaging : An unprecedented secondary C(sp 3 )−H arylation by TAM assistance has been reported, which provides access to functionalized cyclobutane natural product analogues. This strategy features an excellent functional‐group tolerance and a broad substrate scope. Moreover, the first cyclobutane‐BODIPY derivatives have been prepared, proving its synthetic utility.